The Influence of Innovation Culture, Career Development, and Employee Involvement on Employee Performance of PTPN IV Regional II Kebun Adolina Perbaungan District - Febriani, Shalsa; Safina, Wan Dian; Samosir, Suhaila Husna; Habra, M. Dani (PT Mattawang Mediatama Solution, 2025)
AbstractThe phenomenon of employee performance at PTPN IV Regional II Kebun Adolina, Perbaungan District shows a downward trend from year to year. Based on performance assessment data, there are still certain aspects that require attention and strengthening, one of which is through the role of innovation culture, career development, and increasing employee involvement. The purpose of the study was to determine the Influence of Innovation Culture, Career Development and Employee Involvement on Employee Performance at PTP N IV Regional II Kebun Adolina, Perbaungan District. The type of research used in this study is quantitative research. Quantitative research is a research method based on the positivism paradigm, where the data collected is in the form of numbers and analyzed using statistical techniques. The location of the research was conducted at PTPN IV Regional II Kebun Adolina, which is located in Perbaungan District, Serdang Bedagai Regency, North Sumatra Province. Thus, this study will focus on employees in Afd 3 and 4 to understand the culture of innovation, career development, and employee involvement on the performance of PTPN IV Regional II Kebun Adolina Kecamatan employees with a sample of 75 employees. Based on the results of the simultaneous test (F test), it is known that the Fcount value is 26.445 and the significance value is 0.000 which is smaller than 0.05. By using the Ftable value of 3.226 (df1 = 3 and df2 = 71), then Fcount> Ftable, so it can be concluded that Innovation Culture, Career Development, and Employee Involvement simultaneously have a significant effect on Employee Performance at PTPN IV Regional II Kebun Adolina Kecamatan Perbaungan. Keywords: Innovation Culture; Career Development; Employee Performance